ENHANCED CHEMICAL WEATHERING OF ROCKS DURING THE LAST GLACIAL MAXIMUM: A SINK FOR ATMOSPHERIC CO2? - Ludwig W.; Amiotte-Suchet P.; Probst J.L. (My University, 1999)
It has been proposed that increased rates of chemical weathering and the related drawdown of atmospheric CO2 on the continents may have at least partly contributed to the low CO2 concentrations during the last glacial maximum (LGM). Variations in continental erosion could thus be one of the driving forces for the glacial/interglacial climate cycles during Quaternary times. To test such an hypothesis, a global carbon erosion model has been applied to a LGM scenario in order to determine the amount of CO2 consumed by chemical rock weathering during that time. In this model, both the part of atmospheric CO2 coming from silicate weathering and the part coming from carbonate weathering are distinguished. The climatic conditions during LGM were reconstructed on the basis of the output files from a computer simulation with a general circulation model. Only the predicted changes in precipitation and temperature have been used, whereas the changes in continental runoff were determined with an empirical method. It is found that during the LGM, the overall atmospheric CO2 consumption may have been greater than today (by about 20%), mainly because of greater carbonate outcrop area related to the lower sea level on the shelves. This does not, however, affect the atmospheric CO2 consumption by silicate weathering, which alone has the potential to alter atmospheric CO2 on the long-term. Silicate weathering and the concomitant atmospheric CO2 consumption decreased together with a global decrease of continental runoff compared to present-day (both by about 10%). Nevertheless, some uncertainty remains because the individual lithologies of the continental shelves as well as their behavior with respect to chemical weathering are probably not well enough known. The values we present refer to the ice-free continental area only, but we tested also whether chemical weathering under the huge ice sheets could have been important for the global budget. Although glacial runoff was considerably increased during LGM, weathering under the ice sheets seems to be of minor importance.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная